Newborn e raça: fraturas nas visualidades e nas representações - Bonifácio, Solange (2022)
This research aims to investigate the method of photography applied to newborn babies called newborn. Newborn is a photography modality aimed at babies up to fifteen days old and performed by professional photographers. It is about performing, in a qualitative approach, a cartography of imagery production on babies based on the Brazilian historical context. The methodology is cartographic inspiration research produced through the realization and analysis of a bibliographic survey on photography, babies and childhoods, under racial analysis. The corpus is composed of the website of the Brazilian Association of Newborn Photographers and the Newborn section of the magazine "Fhox". The data indicate that, in the production of the modality, there are certain specific procedures and techniques that organize a network of which produce a given visuality forces to babies. In other words, it constitutes a certain image of a baby and, consequently, of black and non-black childhood through techniques directed at the newborn to constitute a performance whose projection focuses on predefined poses, some try to be “the mirror of the uterus”. Thus, also different from other events, such as baby shower, birth, birthdays in which photography is the , record of the ritual, in the case of newborn photography it is established as its own ritual of visuality that prescribes the social and subjectivity(s) roles of each subject by moving out in spaces such as schools, screens of communication equipment, among others.